Technology Adoption and Double-Bottom-Line Performance in Ghanaian Cooperative Financial Institutions: The Moderating Role of Firm Size and Age - Attobrah, Kwasi Poku; Ocansey, Evans Osborn Nene Daker; Amponsah, Emmanuel B. (Archives of Business Research, 2025)
In Ghana, Cooperative Financial Institutions (CFIs) are crucial for extending financial services to underserved communities while achieving financial sustainability. The study sought to investigate the effect of technology adoption on CFIs' double-bottom-line (DBL) performance (simultaneous achievement of financial sustainability and social outreach); to understand how mobile banking, core banking systems (CBS), and digital marketing tools influence CFIs on profitability, membership acquisition and retention, and brand visibility; and, to explore and explain if institutional characteristics shape CFIs' technology adoption outcomes on DBL performance. The study examined views of CFI senior officers and management committee members from all over Ghana and found a positive relationship between technology adoption and financial performance and social performance. Importantly, the findings revealed CFI firm characteristics are important, in that younger CFIs and larger CFIs experienced more benefit to their operational performance through digital technologies than older CFIs and smaller CFIs. While technology adoption was a driver for more financial viability including a more comprehensive brand visibility, social outreach for the CFI was more insightful in demonstrating institutional capacity. Although technology adoption can be a driver for inclusive development, CFIs' readiness to adopt was as critical as the technology itself. Employing a DBL model, this study expands to the body of knowledge on digital transformation in financial cooperative development. It attracts attention to the moderate influence of institution-level determinants on the results of technology adoption for social and financial purposes, offering useful information to regulators, policymakers, and inclusive growth strategies.